Erythroderma caused by anti tuberculoid drug in pulmonary tuberculosis and HIV infected patient: A case report - Dharmawan, Nugrohoaji; Nareswari , Adniana; Fitriani, Fatimah (Journal of Pakistan Association of Dermatologists, 2023)
Erythroderma or exfoliative dermatitis is a cutaneous disease characterized by erythema and scaling affecting more than 90% of body surface area. This can be resulted from malignancy, drug eruption, idiopathic and underlying disease like psoriasis, atopic dermatitis and seborrhoic dermatitis. Patients with HIV/AIDS are prone to drug eruption. A 50 year old man presented to our outpatient clinic with exfoliative scaly skin all over his body after consuming anti-TB therapy. He was diagnosed with lung tuberculosis (TB), human immunodeficiency virus (HIV) infection stage 3. Histopathological examination revealed mild acanthosis and spongiosis in the epidermis, dropping melanin, lymphocyte, histiocyte and perivascular polymorphonuclear (PMN) leukocytes in the dermis. We treated this patient by discontinuing his anti-TB drug, the suspected causative drug, hydrating with intravenous fluid, placing him in warm room and covering him with thin blanket. He was treated with methylprednisolone IV 62.5 mg/24 hours for 5 days, cetirizine tablet 10 mg once daily, topical vaselin applicative twice per day, gentamicin ointments applied on the erosive area twice daily and extra egg white diet 1700 kcal. Our patientâ€™s condition improved after discontinuing anti-TB drugs and receiving systemic corticosteroid as well as topical emollient. Erythroderma due to the first line antitubercular drug is uncommon. It can lead to a serious potentially life threatening problem. Therefore early recognition, early diagnosis and early treatment determine the outcome. Â 